The radiology in the diagnosis and staging of gastric cancer - Zubiaurre, Jorge Leandro (Cirugía del Uruguay, 1988)
It is estimated that gastric cancer, developed in the glandular epithelium of the mucosa, remains confined to her for a long time - up to 10 years - in most cases. If this is true, the chance of detecting lesions in early stages is good (19). Most elevated injuries type I and Ila are of differentiated type, and the time what takes place for them to transform into a cancer advanced is believed to be relatively long. The lesions depressed would also go through multiple episodes of ulceration-healing (malignant cycle) in its slow development course.